2020
DOI: 10.1208/s12249-020-01825-7
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Predictive Dissolution Testing of Montelukast Sodium Formulations Administered with Drinks and Soft Foods to Infants

Abstract: In vitro dissolution testing conditions that reflect and predict in vivo drug product performance are advantageous, especially for the development of paediatric medicines, as clinical testing in this population is hindered by ethical and technical considerations. The aim of this study was to develop an in vivo predictive dissolution test in order to investigate the impact of medicine co-administration with soft food and drinks on the dissolution performance of a poorly soluble compound. Relevant in vitro disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
(69 reference statements)
2
11
0
Order By: Relevance
“…Considering this, dissolution studies were performed under simulated fasted gastric to fasted intestinal conditions and simulated fasted gastric to fed intestinal conditions, and a higher % drug dissolved was observed in the fasted gastric to fed intestinal conditions testing, which is related to a higher drug solubility in fed state simulated media (14). The dissolution results are in accordance with a recent study where montelukast medicine co-administration practices were investigated in a two-stage dissolution approach using a mini-paddle apparatus (9). Similar to the results observed in this study, Martir et al showed that mixing medicines with food and drinks can affect drug product performance, and the in vitro dissolution of montelukast was higher under simulated fed intestinal conditions compared to simulated fasted state conditions (9).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Considering this, dissolution studies were performed under simulated fasted gastric to fasted intestinal conditions and simulated fasted gastric to fed intestinal conditions, and a higher % drug dissolved was observed in the fasted gastric to fed intestinal conditions testing, which is related to a higher drug solubility in fed state simulated media (14). The dissolution results are in accordance with a recent study where montelukast medicine co-administration practices were investigated in a two-stage dissolution approach using a mini-paddle apparatus (9). Similar to the results observed in this study, Martir et al showed that mixing medicines with food and drinks can affect drug product performance, and the in vitro dissolution of montelukast was higher under simulated fed intestinal conditions compared to simulated fasted state conditions (9).…”
Section: Discussionsupporting
confidence: 91%
“…The dissolution results are in accordance with a recent study where montelukast medicine co-administration practices were investigated in a two-stage dissolution approach using a mini-paddle apparatus (9). Similar to the results observed in this study, Martir et al showed that mixing medicines with food and drinks can affect drug product performance, and the in vitro dissolution of montelukast was higher under simulated fed intestinal conditions compared to simulated fasted state conditions (9).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pediatric patients have additional ethical and technical constraints that affect the development of a suitable dosage form; these include the choice of the dosage form and its excipients, palatability, volume of administration, etc. (13). Further complications in the pediatric population arise as a result of the lack of formulations designed for the target pediatric population, which lead to drug manipulation practices (14)(15)(16), such as tablet splitting and crushing, and/or drug products being mixed with small amounts of food or drink vehicles to facilitate administration (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the main intended application of a pediatric PBPK model has been the proposal of initial dosing recommendation for pediatric clinical trials (22). Biorelevant in vitro dissolution studies, which take into account pediatric physiology, have started to appear in the literature (13,(23)(24)(25). The development of pediatric PBPK models focused on oral absorption coupled with in vitro dissolution may lead to discussions around pediatric biopharmaceutics and propose strategies to be used in pediatric drug development for the evaluation of age-related changes on drug product performance (6,8).…”
Section: Introductionmentioning
confidence: 99%